Characteristics of C-, N-DBPs formation from algal organic matter: Role of molecular weight fractions and impacts of pre-ozonation. (1st April 2015) - Zhou, Shiqing; Zhu, Shumin; Shao, Yisheng; Gao, Naiyun
Abstract: Extracellular organic matter (EOM) and intracellular organic matter (IOM) of Microcystis aeruginosa have been reported to contribute to the formation of carbonaceous disinfection by-products (C-DBPs) and nitrogenous disinfection by-products (N-DBPs). Little is known about DBPs formation from different molecular weight (MW) fractions, especially for N -nitrosodimethylamine (NDMA). This study fractionated EOM and IOM into several MW fractions using a series of ultrafiltration membranes and is the first to report on the C-DBPs and N-DBPs formation from chlorination and chloramination of different MW fractions. Results showed that EOM and IOM were mainly distributed in low-MW (<1 KDa) and high-MW (>100 KDa) fractions. Additionally, the low-MW and high-MW fractions of EOM and IOM generally took an important part in forming C-DBPs and N-DBPs, either in chlorination or in chloramination. Furthermore, the effects of pre-ozonation on the formation of DBPs in subsequent chlorination and chloramination were also investigated. It was found that ozone shifted the high-MW fractions of EOM and IOM into lower MW fractions and increased the C-DBPs and N-DBPs yields to different degrees. As low-MW fractions are more difficult to remove than high-MW fractions by conventional treatment processes, therefore, activated carbon adsorption, nanofiltration (NF) and biological treatment processes can be ideal to remove the low-MW fractions and minimize the formation potential of C-DBPs and N-DBPs. Moreover, the use of ozone should be carefully considered in the treatment of algal-rich water. Graphical abstract: Highlights: Algal organic matters were fractionated into six molecular weight (MW) fractions. Low-MW and high-MW fractions contributed to most disinfection by-products (DBPs). Pre-ozonation shifted the high-MW to low-MW fractions and increased DBPs yields.